On the competition in phase formation during the crystallisation of Al-Ni-Y metallic glasses. (15th September 2016) - Styles, M.J.; Sun, W.W.; East, D.R.; Kimpton, J.A.; Gibson, M.A.; Hutchinson, C.R.
Abstract: Glassy metals exhibit a range of interesting properties including high strength and corrosion resistance, but often have poor toughness and tensile ductility in the fully amorphous state. It has been shown that combinations of desirable properties can be achieved by the partial crystallisation of glass-forming alloys, either during controlled solidification or by annealing a fully amorphous glass. The aim of this investigation is to understand the competition in phase formation during the crystallisation of metallic glasses in the Al-Ni-Y system. High-resolution, in situ synchrotron powder diffraction has been used to quantitatively follow the evolution of phases in 5 different alloys between Al87 Ni9 Y4 and Al75 Ni15 Y10, as they were continuously heated to melting and subsequently cooled back to ambient temperature. Upon heating, the first crystallisation product was found to vary from FCC Al to the intermetallic Al9 Ni2 phase with increasing Ni concentration. In addition, the crystallisation sequence also changed from a two-stage to a three-stage process. High number densities of crystallites (∼10 23  m −3 ) were observed initially for both FCC Al and Al9 Ni2 . Upon cooling, the partially disordered Al9 Ni3 Y phase was found to form preferentially over the intermetallic phases observed during heating. The difference in competition in phase formation during heating and cooling are discussed in terms of nucleation barriers calculated using a recent thermodynamic assessment of the Al-Ni-Y system. The role of compositional heterogeneities in the as-quenched glasses and long-range diffusion on the nucleation process is discussed. Graphical abstract: High-resolution, in situ synchrotron powder diffraction has been used to quantitatively follow the evolution of phases in 5 different alloys between Al87 Ni9 Y4 and Al75 Ni15 Y10, as they were continuously heated to melting and subsequently cooled back to ambient temperature. Upon heating, the first crystallisation product was found to vary from FCC Al to the intermetallic Al9 Ni2 phase with increasing Ni concentration. In addition, the crystallisation sequence also changed from a two-stage to a three-stage process. High number densities of crystallites (∼10 23  m −3 ) were observed initially for both FCC Al and Al9 Ni2 . The difference in competition in phase formation during heating and cooling are discussed in terms of nucleation barriers calculated using a recent thermodynamic assessment of the Al-Ni-Y system. The role of compositional heterogeneities in the as-quenched glasses and long range diffusion on the nucleation process is discussed.